Vascular dysfunction in CAA in the presence of cardiovascular risk factors: The role of the mitochondria and therapeutic approaches: Molecular and cell biology/mitochondrial function/energetics. (7th December 2020) - Parodi‐Rullan, Rebecca M.; Sone, Je Yeong; Fossati, Silvia
Abstract: Background: The accumulation of amyloid‐β (Aβ) on the brain vasculature, known as Cerebral Amyloid Angiopathy (CAA), induces vascular dysfunction contributing to neurodegeneration. Cardiovascular (CV) risk factors, which are also mediators of vascular dysfunction and may increase the risk for developing Alzheimer's Disease and dementia, may potentiate CAA‐mediated neurovascular pathology. Mitochondria are key cellular organelles that have a dual role as mediators of cell survival and death and have an important role in disease pathogenesis. However, the role of brain endothelial mitochondria in vascular amyloidosis complicated with CV risk factors is unknown. The carbonic anhydrase inhibitors (CAi) methazolamide and acetazolamide were able to reduce amyloid‐induced cell death and mitochondrial dysfunction. Our work focuses on understanding the mechanisms of vascular dysfunction induced by Aβ complicated with CV risk factors. We aim to understand the protective role of CAi in preventing the pathological changes associated to neurovascular dysfunction and neurodegeneration. Method: Immortalized human cerebral microvascular endothelial cells (ECs) were used to study the molecular changes that occur in the cerebral vasculature during amyloid challenge complicated with CV risk factors, such as hyperhomocysteinemia (HHC). We then tested CAi and their potential to prevent cell death and mitochondrial dysfunction in ECs challenged with Aβ in the presence or absence of CV risk factors such as HHC. Result: Aβ and HHC increased EC barrier permeability and that the presence of HHC worsened amyloid‐induced barrier permeability. Aβ‐induced EC apoptosis was reduced by treatment with CAi. We further demonstrate that both Aβ and HHC decrease mitochondrial basal respiration. The presence of Aβ induces cytochrome‐c release, mitochondrial membrane potential loss, and ROS production which were reduced by treatment with CAi. Conclusion: HHC and Aβ induce brain microvascular EC dysfunction and increase permeability of the EC barrier. Aβ induces cell death and mitochondrial dysfunction, which are both prevented by CAi. We also demonstrate that CV risk factors, specifically HHC, induce mitochondrial dysfunction on brain ECs which could further contribute to neurovascular dysfunction and neurodegeneration observed in CAA. Our studies suggest that CAi could serve as a novel therapeutic strategy towards vascular dysfunction during CAA complicated with CV risk factors.